EXPERIMENTAL INVESTIGATIONS OF REINFORCED CONCRETE STRUCTURES OF HYDRAULIC STRUCTURES WITH BLOCK SEAMS, ENHANCED BY THE EXTERNAL REINFORCEMENT SYSTEM - Rubin, O.D.; Lisichkin, S.E.; Frolov, K.E. (Stroitelʹnaâ mehanika inženernyh konstrukcij i sooruženij (Online), 2018)
A method of strengthening reinforced concrete structures by external reinforcement systems based on carbon fiber is widely used. Significant experience is accumulated in industrial and civil construction; there is also a certain experience of strengthening reinforced concrete structures of hydraulic structures. It was necessary to conduct experimental studies to justify technical solutions for strengthening the reinforced concrete structures of hydraulic structures. A characteristic feature of reinforced concrete structures of hydraulic structures is the mandatory availability of inter-block construction joints, which are caused by the need to build massive hydraulic structures with tiers and blocks with interruptions in concreting. Previously studies of reinforced concrete structures strengthened by composite materials were conducted without taking into account the block structure. The results of experimental studies of reinforced concrete beam structures of hydraulic structures reinforced with carbon strips having horizontal and vertical inter-block building seams are presented in the article. Experimental studies of a series of reinforced concrete beam-type models made of concrete of class B15 with longitudinal reinforcement from two bars. Their diameter is 10 mm and class is A500C (percentage of reinforcement 0.39%). The used concrete class is B25 with longitudinal reinforcement of three bars of diameter 12 mm and class A500C (percentage of reinforcement 0.84%). Their inter-block construction joints is before their strengthening and after reinforcement by longitudinal and transverse carbon composite tapes. In this case, a special type of cracking was recorded, in which cracks propagate along vertical and horizontal inter-block building seams. Due to the strengthening of reinforced concrete structures with carbon composite strips, the strength of the structures has increased, on average, by 1.78 times.